Effect of sildenafil on digital ulcers in systemic sclerosis: analysis from a single centre pilot study. Issue 8 (8th November 2009) - Brueckner, Claudia S; Becker, Mike O; Kroencke, Thomas; Huscher, Doerte; Scherer, Hans Ulrich; Worm, Margitta; Burmester, Gerd; Riemekasten, Gabriela
Abstract : Objective: In this pilot study, the effect of sildenafil on digital ulcer (DU) healing and related clinical symptoms was analysed. Methods: A total of 19 patients with systemic sclerosis (SSc) were treated with maximally tolerated sildenafil doses up to 6 months. Primary outcome was the healing of DUs. Changes in other clinical symptoms were also evaluated. Results: In all, 49 DUs were present at baseline; this decreased to 17 ulcers (p<0.001) at the end of sildenafil treatment. Furthermore, the visual analogue scale (VAS) score for Raynaud's phenomenon (RP), pain and activity improved (p=0.003, p=0.002 and p=0.05, respectively). A total of 9 patients developed 12 new DUs during sildenafil treatment. Conclusions: This study indicates an effect of sildenafil on DU healing in patients with SSc and an improvement of RP and associated symptoms that should be validated in controlled studies.